Political Science of Religion - Potz, Maciej. author. (orcid)0000-0003-4546-5699 Link aut Link
XIII, 187 p. 4 illus.
Keywords: This book introduces political science of religion – a coherent approach to the study of the political role of religion grounded in political science. In this framework, religion is viewed as a political ideology providing legitimation for power and motivating political attitudes and behaviors of the public. Religious organizations are political actors negotiating the political system in the pursuit of their faith-based objectives. Religion is thus interpreted as a power resource and religious groups as political players. The theoretical framework developed in the first part is applied to the study of theocracies and contemporary democracies, based on the case studies of Poland and the USA. The empirical analysis of resources, strategies and opportunities of religious actors demonstrates their ability to influence the politics of democracies and non-democracies alike. Using a multilevel approach, the book seeks to explain this tremendous political potential of religion. Maciej Potz is a full professor of Political Science at the Department of Political Systems, Faculty of International and Political Studies, University of Łódź, Poland. His research focuses on political theory and political science of religion. As a Foundation for Polish Science scholar he did research on Shaker and Mormon theocracies in the USA. His publications include monographs on the relations between religion and the state in the USA and on American theocracies, as well as several articles, including in Religion, State and Society, Journal of Political Power, Politics and Religion Journal. .